The Influence of Traditional Medicine and Religion on Discontinuation of ART in an Urban Informal Settlement in Nairobi - Unge, Christian; Ragnarsson, Anders; Ekström, Anna Mia; Indalo, Dorcus; Belita, Alice; Carter, Jane; Ilako, Festus; Södergård, Björn (Taylor & Francis Online)
Objective: The objective of this study was to explore the influence of traditional medicine and religion on discontinuation of antiretroviral therapy (ART) in one of Africa's largest informal urban settlement, Kibera, in Nairobi, Kenya. Methods: Semi-structured face-to-face interviews were conducted with 20 patients discontinuing the African Medical and Research Foundation (AMREF) ART program in Kibera due to issues related to traditional medicine and religion. Results: Traditional medicine and religion remain important in many people's lives after ART initiation, but these issues are rarely addressed in a positive way during ART counseling. Many patients found traditional medicine and their religious beliefs to be in conflict with clinic treatment advice. Patients described a decisional process, prior to the actual drop-out from the ART program that involved a trigger event, usually a specific religious event, or a meeting with someone using traditional medicine that influenced them to take the decision to stop ART. Conclusion: Discontinuation of ART could be reduced if ART providers acknowledged and addressed the importance of religious issues and traditional medicine in the lives of patients, especially in similar resource-poor settings. Telling patients not to mix ART and traditional medicine appeared counter-productive in this setting. Introducing an open discussion around religious beliefs and the pros and cons of traditional medicine as part of standard counseling, may prevent drop-out from ART when side effects or opportunistic infections occur.
Keywords: Traditional medicine; Antiretroviral therapy; ART; Religion; Drop out; HIV; Kenya; Kibera; Urban informal settlement; Slum; AMREF